2015
DOI: 10.1038/ijo.2015.42
|View full text |Cite
|
Sign up to set email alerts
|

Growth trajectories in early childhood, their relationship with antenatal and postnatal factors, and development of obesity by age 9 years: results from an Australian birth cohort study

Abstract: Efforts to prevent childhood obesity may need to be embedded within population-wide strategies that also pay attention to healthy weight for women in their reproductive years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
96
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(116 citation statements)
references
References 38 publications
(48 reference statements)
16
96
2
Order By: Relevance
“…Giles et al reported four distinct BMI Z ‐score trajectories from birth to age 3 years among 557 Australian participants. These four trajectory groups, which were characterized by birth size and postnatal growth in the first 6 months of life, were labeled as “low” (lower BMI Z ‐score at birth and substantial decrease until 6 months), “intermediate” (lower BMI Z ‐score at birth and slight decrease until 6 months), “high” (higher BMI Z ‐score at birth and maintenance until 6 months) and “accelerating” (higher BMI Z ‐score at birth and increase until 6 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giles et al reported four distinct BMI Z ‐score trajectories from birth to age 3 years among 557 Australian participants. These four trajectory groups, which were characterized by birth size and postnatal growth in the first 6 months of life, were labeled as “low” (lower BMI Z ‐score at birth and substantial decrease until 6 months), “intermediate” (lower BMI Z ‐score at birth and slight decrease until 6 months), “high” (higher BMI Z ‐score at birth and maintenance until 6 months) and “accelerating” (higher BMI Z ‐score at birth and increase until 6 months).…”
Section: Discussionmentioning
confidence: 99%
“…Group‐based trajectory modeling enables the data themselves to divide a study population into subgroups that present distinct patterns and to fit its own trajectory models for each of those subgroups . Several studies have applied the group‐based trajectory approach to identify distinct weight gain patterns . However, few studies have examined the association between diverse weight gain trajectory patterns in the first 2 years of life and adiposity levels later in life.…”
Section: Introductionmentioning
confidence: 99%
“…1 -12 Previous studies have identified 3 broad types of trajectories: a majority group with "healthy" BMI throughout childhood, groups who develop BMI in the overweight range at some point during childhood, and those with BMI in the overweight or obese range throughout childhood. 1 -6 Underlying influences on different patterns of BMI development are not well understood, but factors reported to predict childhood BMI trajectories include mother's BMI, 1,3,5,6,8,10,11 smoking during pregnancy, 1,5,6 and sociodemographic background. 1 -5, 12 Previous work suggests that a range of early life factors including infant feeding, diet, physical activity, and family routines are associated with child overweight and obesity.…”
mentioning
confidence: 99%
“…53,54 Latent class growth modeling is one method used recently to distinguish groups of children with biologically distinct growth trajectories and estimate the effects of prenatal and postnatal exposures on the odds of membership in a specific growth trajectory group. 55 Future research could benefit from utilizing these advanced methods of studying early life growth patterns.…”
Section: Discussionmentioning
confidence: 99%